Veblen : the making of an economist who unmade economics - Camic, Charles (Harvard University Press, 2020)
"Thorstein Veblen's analysis of America's parasitic upper class, which plunders its wealth from productive workers, is widely attributed to his outsider status. But Charles Camic shows that Veblen's ideas did not derive from social marginality. Veblen was a professional economist whose fierce social critique was the work of an academic insider"--